Easy homemade pottery : make your own stylish decor using polymer and air-dry clay - Stone, Francesca (Page Street Publishing, 2020)
Planters, Vases, Dishes and More, Without a Pottery Studio! You'll be amazed by what you can create with polymer and air-dry clay. These affordable, easy-to-find clays present endless possibilities for artisan-quality home decor and gifts. Francesca Stone, creator of the decor blog Fall For DIY, presents simple step-by-step techniques for shaping and decorating clay with just a few household tools. All final pieces can be air-dried or baked in a standard home oven. Featuring a gorgeous, modern palette of natural colors, these projects are deceptively easy and effortlessly chic. Personalize your home with practical and beautiful items like the Terra-Cotta Jewelry Dish, Hanging Herb Garden Planter and Salt-and-Pepper Pinch Pot. Get creative with color and geometric shapes in home accents such as the Color-Block Photo Holder and Abstract Floral Block Platter. This book is the perfect primer to start making beautiful clay pieces at home and get that handmade ceramic look without the expenses and challenges of traditional pottery.